PENGARUH PARTISIPASI PEREMPUAN TERHADAP PEREKONOMIAN KOTA/KABUPATEN DI SUMATERA BARAT - Alfira Azzahra; Novya Zulva Riani (Universitas Negeri Padang, 2025)
The purpose of this study is to analyze the influence of women as professionals, women's involvement in parliament, and women's income contributions on the economy of cities/regencies in West Sumatra. This research utilizes secondary data sourced from the Central Bureau of Statistics (BPS) from 2017 to 2022. The study employs an equation model using the Random Effect Model (REM). The findings reveal that women as professionals have a positive and significant impact on the economy, women's involvement in parliament has no impact on the economy, and women's income contributions have a positive and significant effect on the economy of cities/regencies in West Sumatra.